Omni wheel robot movement exploration using a control system for military surveillance with integrated sensor - Jeffri Kurniawan; Mokhammad Syafaat; Kasiyanto Kasiyanto; Dekki Widiatmoko; Rafi Maulana; Zihar Nanggala Putra (LPPMPK- Universitas Muhammadiyah Cileungsi, 2025)
Industry 4.0 is bringing about a rapid advancement in technology, particularly in the military industry. This robot was designed to reduce danger to TNI members while monitoring military operations more swiftly and safely. The application of IMU sensors for acceleration movements, measurement of control system error values, and trajectory tracking with multiple pathways are the three modes of the robot control system observed in this study. We assess each of these modes using an analytical observational method. In addition to an MPU 6050 ultrasonic and gyro sensor to detect movement using an accelerometer and gyroscope, the robot is equipped with a rotational encoder sensor to link the DC motor rotation. The PID control approach uses inverse kinematics to regulate the DC motor. The exam is administered on a track that has squares, triangles, and circles as obstacles. According to test results, the tachometer's inaccuracy rate in RPM is about 1.2% higher than the rotary encoder. The movement success percentage for the omni-wheel robot is 89.31%. Square trajectories have an average error rate of 11%, circular trajectories of 15%, and triangular trajectories of 4.17%. The motor rotation speed is most stable along the triangle path. Overall, this study demonstrates the accuracy and speed with which a mobile omni-wheel robot equipped with a control system can peek. This could raise military operations' level of efficiency and safety